Conservation implications of omitting narrow‐ranging taxa from species distribution models, now and in the future. Issue 11 (5th September 2014) - Platts, Philip J.; Garcia, Raquel A.; Hof, Christian; Foden, Wendy; Hansen, Louis A.; Rahbek, Carsten; Burgess, Neil D.; Fitzpatrick, Matt
Abstract Aim Species distribution modelling (SDM) is commonly used to predict spatial patterns of biodiversity across sets of taxa with sufficient distributional records, while omitting narrow‐ranging species due to statistical constraints. We investigate the implications of this dichotomy for conservation priority setting in Africa, now and in the future. Location Sub‐Saharan Africa (excluding islands). Methods We use multivariate ordination to characterize climatic niches of 733 African amphibians, distinguishing between species eligible for large‐scale correlative SDM (≥ 10 records at 1° resolution) and those omitted due to insufficient records. Species distributions are projected under current and future climates using simple niche envelopes. Empirical priorities are derived separately on the eligible and omitted sets and compared with three existing large‐scale conservation schemes. Results Of the 733 amphibian species, 400 have too few records for correlative SDM, including 92% of those threatened with extinction (VU/EN/CR). Omitted species typically occupy topographically complex areas with cooler, wetter and less seasonal climates, which are projected to experience lower rates of climatic change. Priorities derived from omitted species have greater congruence with existing conservation schemes. Under future climate, priorities for eligible species shift towards those for omitted species. Similarly, while omitted species often lose climate space at 1° resolution, persistent populations tend to coincide with existing conservation schemes. Main conclusions Under current climate, statistical restrictions on SDM systematically downplay important sites for narrow‐ranging and threatened species. This issue spans taxonomic groups and is only partially mitigated by modelling at finer scales. Effective biodiversity conservation, now and in the future, relies on our capacity to project geographic determinants of all species, and thus, a wider range of approaches is essential. We conclude, however, that future persistence among narrow‐ and wide‐ranging species alike will be highest within sites already identified for conservation investment and that the focus on these sites ought to be maintained.